2020
DOI: 10.21203/rs.3.rs-97718/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on The Symptoms and Esophageal Motility Characteristics of Gastroesophageal Reflux Disease Patients with Obesity

Abstract: Background: Previous studies have shown that obesity affects the occurrence and development of GERD, GERD is also one of the many complications of obesity. However, few prior studies have evaluated the symptoms and esophageal motility characteristics of GERD patients with obesity. The purpose of this study was to assess the symptoms and esophageal motility characteristics of gastroesophageal reflux disease (GERD) patients with obesity and the relationship between symptoms and esophageal motility results. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…These patients often have poor response to PPI treatment and are diagnosed as RGERD. [17] Studies have shown that RGERD patients have simultaneous decreases in the pressure of the upper and lower esophageal sphincters, with weak acid reflux and nonacid reflux being predominant, which is also the reason for the poor response to PPI treatment. [18] The "2020 Chinese Expert Consensus on Gastroesophageal Reflux Disease" suggests that for RGERD patients, it is recommended to switch to a different type of PPI and maintain double-dose treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These patients often have poor response to PPI treatment and are diagnosed as RGERD. [17] Studies have shown that RGERD patients have simultaneous decreases in the pressure of the upper and lower esophageal sphincters, with weak acid reflux and nonacid reflux being predominant, which is also the reason for the poor response to PPI treatment. [18] The "2020 Chinese Expert Consensus on Gastroesophageal Reflux Disease" suggests that for RGERD patients, it is recommended to switch to a different type of PPI and maintain double-dose treatment.…”
Section: Discussionmentioning
confidence: 99%